Consecutive Ring Expansion and Contraction for the Synthesis of 1‐Aryl Tetrahydroisoquinolines and Tetrahydrobenzazepines from Readily Available Heterocyclic Precursors. (17th April 2018) - Hill, Jessica E.; Matlock, Johnathan V.; Lefebvre, Quentin; Cooper, Katie G.; Clayden, Jonathan
Abstract: Tetrahydroisoquinolines and tetrahydrobenzazepines were prepared by acid‐promoted ring contraction of cyclic ureas, which were themselves formed by ring expansion of indolines and tetrahydroquinolines. The consequent overall one‐carbon insertion reaction gives these 6‐ and 7‐membered heterocyclic scaffolds in three steps from readily available precursors. Other ring sizes may be formed by an alternative elimination reaction of bicyclic structures. Scalability of the method was demonstrated by operating it in a flow system.